Goods medium adaptability corrosion evaluation method and system based on chemical tanker liquid cargo tank

By using a multi-stage corrosion test method to evaluate the suitability of stainless steel materials to cargo medium in chemical ships, the problems of unclear and inaccurateness in the prior art are solved, and the accurate suitability evaluation of stainless steel materials is achieved and corrosion rate analysis.

CN119164867AActive Publication Date: 2024-12-20CHINA CLASSIFICATION SOCIETY SHANGHAI CODE RES INST
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411328833.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-20
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The prior art lacks a cargo adaptability evaluation system and corrosion performance testing method for stainless steel materials for chemical ships and cargo tanks, resulting in unclear and inaccurate problems.

Method used

The corrosion evaluation method for cargo medium adaptability based on the chemical ship's liquid cargo tank is adopted, and the corrosion test results of the stainless steel standard samples are obtained through the first corrosion test method, and the second corrosion test is decided based on the results, combining the high-temperature accelerated corrosion method and the transport ship Comparative analysis of corrosion methods at actual design loading temperature to evaluate the suitability of stainless steel materials to different product media.

Benefits of technology

It realizes the accurate fitting evaluation of stainless steel materials for different goods media, improves the accuracy of corrosion rate analysis, ensures the suitability of goods and acceptable corrosion allowance, which is of great significance to material selection and product list determination. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119164867A_ABST
    Figure CN119164867A_ABST
Patent Text Reader

Abstract

The invention provides a cargo medium adaptability corrosion evaluation method and system based on a chemical tanker liquid cargo tank. The method comprises the following steps: acquiring a corrosion test result of a stainless steel standard sample in a first cargo medium by adopting a first corrosion test method; determining whether a second corrosion test method is carried out or not according to the corresponding first corrosion degree obtained by the first corrosion test method, and judging whether the cabin body thickness of the ship transportation cabin is processed for the corresponding goods medium or not by adopting the first corrosion degree or the second corrosion degree according to the judgment condition. According to the method, two different corrosion methods are adopted to judge the fitting degree of a certain goods medium made of a stainless steel material, the corrosion rate is analyzed to obtain the corresponding index, and fitting evaluation is performed according to the index to obtain the fitting evaluation result; and whether the goods are suitable for loading the stainless steel of the cargo tank of the chemical tanker is determined according to the fitting evaluation result, so that the fitting corrosion evaluation of the stainless steel goods is accurate and effective.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of suitability assessment of liquid cargo tanks of chemical tankers, and in particular to a method and system for assessing suitability corrosion of cargo media based on liquid cargo tanks of chemical tankers. Background Art

[0002] Austenitic stainless steel is widely used in the shipbuilding industry due to its good corrosion resistance, paramagnetism and biocompatibility. However, this type of steel has disadvantages such as low strength and high cost in the shipbuilding industry, which limits the scope of use of the material. Duplex stainless steel can effectively solve the above two shortcomings. Duplex stainless steel has good strength, toughness, weldability and corrosion resistance. After years of development, duplex stainless steel has become the fourth stainless steel system alongside austenitic, ferritic and martensitic systems. It has been widely used in petrochemical, papermaking, construction, shipbuilding and marine engineering.

[0003] Nickel-saving duplex stainless steel has a yield strength more than twice that of austenitic stainless steel. As a ship structure material, it can effectively reduce plate thickness and reduce costs, which meets the needs of a resource-saving society, green ships and lightweight ships. However, due to the artificial reduction of nickel addition in the steelmaking process, this inevitably leads to a decrease in the corrosion resistance of the material. The existing technology has not yet specified a cargo suitability assessment system and a corrosion performance testing method or system for stainless steel materials in chemical tanker liquid cargo tanks. Summary of the invention

[0004] Purpose of the invention: In view of the problems existing in the above-mentioned prior art, the present invention constructs a corrosion assessment method and system for cargo medium suitability based on the liquid cargo tank of a chemical tanker, which solves the problem of unclear and inaccurate suitability of stainless steel materials in liquid cargo tanks for different types of cargoes.

[0005] Technical solution: The present invention provides a method for evaluating the suitability of cargo medium corrosion in a liquid cargo tank of a chemical tanker, the method comprising:

[0006] Using a first corrosion test method to obtain corrosion test results of a stainless steel standard sample in a first product medium, and then obtaining a corresponding first corrosion degree and a first corrosion rate;

[0007] Determine whether to perform the second corrosion test method according to the first corrosion degree corresponding to the first corrosion test method, specifically:

[0008] Calculate the first corrosion degree of the corresponding stainless steel standard sample according to the corrosion test result of the stainless steel standard sample;

[0009] If the first corrosion degree of the corresponding stainless steel standard sample is large, the stainless steel standard sample and the comparison sample are tested in the second cargo medium using the second corrosion test method under the same parameters to obtain the corrosion test results of the stainless steel standard sample and the comparison sample in the second cargo medium, and then the second corrosion degree and the second corrosion rate corresponding to the second cargo medium are obtained, and the second corrosion degree and the second corrosion rate are used to determine whether to process the tank hull thickness of the chemical tanker liquid cargo tank for the corresponding first cargo medium and the second cargo medium. Otherwise,

[0010] If the first corrosion degree of the corresponding stainless steel standard sample is small, the first corrosion degree and the first corrosion rate are directly used to determine whether to process the thickness of the ship transport warehouse for the corresponding first cargo medium and second cargo medium;

[0011] Among them, the first corrosion test method is a high temperature accelerated corrosion method, and the second corrosion test method is a comparative analysis corrosion method of the transport ship at the actual design loading temperature.

[0012] Further, including:

[0013] The first corrosion test method includes standard sample setting, sample condition setting, corrosion test process and display test results, specifically:

[0014] Standard sample setting: Cut three duplex stainless steels of the same size and roughness as the stainless steel standard samples, and obtain the exposed surface area S and the mass W before the test. 11 ;

[0015] Sample condition setting: including a temperature control device, the temperature control device at least including a heater and a timer; an experimental container containing a first commodity medium, the solution volume of the first commodity medium is obtained according to the surface area of ​​the stainless steel standard sample, and a corresponding stainless steel standard sample is placed in each experimental container;

[0016] Corrosion test process: place the first cargo medium in the corresponding experimental container; start the temperature control device to heat the first cargo medium to boiling, and after the first cargo medium boils, put in the corresponding stainless steel standard sample and start timing, and the continuous boiling time T1 is set to 24h;

[0017] The stainless steel standard sample is taken out from the first product medium, and is brushed in running water to remove corrosion products on the surface of the sample. After drying, the post-test mass W of the stainless steel standard sample is obtained. 12 ;

[0018] Display test results: Calculate the first corrosion degree according to the image of the stainless steel standard sample after the test and obtain the first corrosion rate according to the corresponding mass.

[0019] Further, including:

[0020] The first product medium includes: formic acid with a mass percentage concentration of not less than 98% m / m; capric acid with a mass percentage concentration of not less than 99% m / m; saturated citric acid aqueous solution lactic acid with a mass percentage concentration between 85% and 90% m / m; saturated urea aqueous solution acetic anhydride with a mass percentage concentration of not less than 98.5% m / m; acrylic acid with a mass percentage concentration greater than 99% m / m; saturated aluminum sulfate solution with a mass content of 200g / L; saturated aluminum chloride / hydrochloric acid solution; saturated ammonium sulfate aqueous solution; ammonium thiosulfate solution with a mass percentage concentration of 60% m / m; saturated ferric chloride / hydrochloric acid solution; saturated sodium bisulfite aqueous solution; liquid; 99.5% m / m n-butyric acid; 98% m / m chloroacetic acid; 98% m / m 3-chloropropionic acid; a mixture of 64% m / m n-pentanoic acid and 36% m / m 2-methylbutyric acid; phosphoric acid greater than 99% m / m; propionic acid greater than 99.5% m / m; trimethylacetic acid at 99% m / m; saturated aqueous sodium hydroxide solution; 98% m / m allyl chloride and greater than 99.0% m / m benzyl chloride.

[0021] Further, including:

[0022] The calculation formula of the first corrosion rate is expressed as:

[0023]

[0024] The first corrosion rate is used as the first condition for evaluating whether the stainless steel material corresponding to the stainless steel standard sample is suitable for the corresponding product medium, and it is set that when CR1≤100g / (m 2 h), the stainless steel material corresponding to the stainless steel standard sample meets the first condition.

[0025] Further, including:

[0026] The corresponding first corrosion degree obtained according to the first corrosion test method includes:

[0027] Preprocessing the images of the stainless steel standard samples obtained according to the first corrosion test method at different times, wherein the preprocessing includes image screening, image downsampling, and image enhancement performed according to different commodity media, and the different times refer to the time corresponding to the completion of the first corrosion test method, and the image enhancement is obtained according to the result of image downsampling;

[0028] Calculate the information entropy corresponding to the enhanced image after image enhancement under different first commodity media, obtain the weight corresponding to the enhanced image according to the information entropy, and fuse the enhanced image corresponding to each image according to the weight to obtain the final enhanced image;

[0029] Obtaining the eroded area corresponding to the final enhanced image, and obtaining the pixel value of each pixel in the eroded area;

[0030] Calculate the corrosion intensity of the corresponding stainless steel standard sample under the commodity medium according to the pixel value of each pixel point and the corresponding color value;

[0031] Set the corrosion level, and determine the first corrosion degree according to the corrosion intensity and the preset corrosion intensity threshold. If the corrosion intensity threshold is set to [0,10], the corresponding corrosion level is less than 5, and is set as the first corrosion degree is small. The corresponding corrosion level is greater than or equal to 5, and is set as the first corrosion degree is large.

[0032] Further, including:

[0033] The image screening specifically includes: eliminating the abnormal first corrosion rates obtained by the first corrosion test method for three stainless steel standard samples under the same first commodity medium, and deleting the sample images corresponding to the abnormal first corrosion rates. The method for determining the abnormal first corrosion rates is: calculating the pairwise differences among the three first corrosion rates obtained by the first corrosion test method for the three stainless steel standard samples, finding the two first corrosion rates corresponding to the smallest absolute value of the difference, and obtaining the corresponding abnormal first corrosion rates according to the box plot method.

[0034] Further, including:

[0035] The directly using the first corrosion degree and the first corrosion rate to judge whether to process the thickness of the ship transport warehouse for the corresponding first cargo medium and second cargo medium includes:

[0036] The corrosion level serves as the second condition for evaluating whether the stainless steel material corresponding to the stainless steel standard sample is suitable for the corresponding cargo medium. When the corrosion level is not greater than 3, it meets the second condition. Only when both the first and second conditions are met can it be determined that the chemical tanker liquid cargo tank corresponding to the stainless steel standard sample is suitable for the corresponding cargo medium, and whether the corrosion allowance is allowed to be reduced is obtained based on the first corrosion rate.

[0037] Further, including:

[0038] The second corrosion test method includes standard sample setting, sample condition setting, corrosion test process and display test results, specifically:

[0039] Standard sample setting: three duplex stainless steels of two different types with the same size and roughness are cut, and the stainless steel in the first corrosion test method is used as the stainless steel standard sample, and another different type of duplex stainless steel is used as a comparison sample, thereby obtaining the exposed surface area S and the mass W before the test 21 ;

[0040] Sample condition setting: including a temperature control device, the temperature control device at least including a heater and a timer; an experimental container containing a second commodity medium, the solution volume of the second commodity medium is obtained according to the surface area of ​​the stainless steel standard sample and the comparative sample, and a corresponding stainless steel standard sample and comparative sample are placed in each experimental container;

[0041] Corrosion test process: Place the second product medium in the corresponding experimental container; start the temperature control device to heat the second product medium to the corresponding loading temperature, put in the corresponding stainless steel standard sample and comparison sample, start timing, and let it stand for T 21 After 1 hour, the stainless steel standard sample and the comparative sample were taken out, cleaned and weighed to obtain W 22 ;

[0042] Then, the corresponding stainless steel standard samples and comparison samples were placed back in the above test environment and left to stand for T 22 After 12 hours, the stainless steel standard sample was taken out, cleaned and weighed to obtain W. 23 ;

[0043] Display test results: calculate the second corrosion degree based on the tested stainless steel standard sample and the comparison sample, and obtain the second corrosion rate at different transfer temperatures and under different second cargo media based on the corresponding mass.

[0044] Further, including:

[0045] The second cargo medium includes: concentrated sulfuric acid with a mass concentration of 98% m / m, nitric acid with a mass concentration between 65%-68% m / m, and phosphoric acid with a mass concentration of 53% m / m, and the loading temperatures include: 30°C, 40°C and 50°C.

[0046] Further, including:

[0047] The calculation formula of the second corrosion rate corresponding to different standing times is expressed as:

[0048]

[0049] According to the above calculation formula, the corrosion rates of different second cargo media of the stainless steel standard sample at different loading temperatures are obtained; and the corrosion rates of different second cargo media of the comparison sample at different loading temperatures are obtained, and the corrosion rates corresponding to the two samples are compared and analyzed, and then combined with the loading temperature as the first condition for evaluating whether the comparison stainless steel can replace the standard stainless steel to be suitable for the cargo medium.

[0050] Further, including:

[0051] The calculation of the second corrosion degree according to the tested stainless steel standard sample and the comparative sample comprises:

[0052] Obtain the thickness of the standard sample and the comparison sample obtained from the same product medium at the same loading temperature after the test. The thickness of the single standard sample is recorded as D1, and the thickness of the comparison sample is recorded as D2;

[0053] The standard thickness under the same conditions obtained according to relevant standards is recorded as standard H;

[0054] Calculate the difference between the thickness D1 and D2 and the standard thickness H for comparison; specifically, if |D1-H|≤|D2-H|, then the first weight of the standard sample is greater than the corresponding weight of the comparison sample, and the first weight of the standard sample is a parameter for measuring the adaptability of the standard sample and the comparison sample;

[0055] According to the corrosion area corresponding to the standard sample and the comparison sample obtained from the same cargo medium at the same loading temperature, the corrosion area occupancy rate is obtained, which is recorded as R1 and R2 respectively.

[0056] If R1≤R2 and both are less than the occupancy setting threshold, the second adaptation weight of the standard sample is greater than the corresponding weight of the comparison sample, and the second adaptation weight is a parameter for measuring the adaptation capabilities of the standard sample and the comparison sample;

[0057] If R1≤R2 and R2 is not less than the occupancy setting threshold, the second weight of the comparison sample is set to zero.

[0058] If R1≤R2 and both are not less than the occupancy rate setting threshold, then neither the standard sample nor the comparison sample is considered as suitable material.

[0059] If R1>R2 and both are less than the occupancy setting threshold, the second weight of the comparison sample is greater than the corresponding weight of the standard sample.

[0060] If R1>R2 and R1 is not less than the occupancy setting threshold, the second weight of the standard sample is set to zero.

[0061] If R1>R2 and both are not less than the occupancy rate setting threshold, then neither the standard sample nor the comparison sample can be used as suitable materials;

[0062] The second corrosion degree of the standard sample and the comparison sample to a certain cargo medium at different loading temperatures is obtained comprehensively according to the first adaptation weight and the second adaptation weight, which serves as the second condition for whether the comparison stainless steel can replace the standard stainless steel to be suitable for the cargo medium.

[0063] Further, including:

[0064] Using the second corrosion degree and the second corrosion rate to determine whether to process the thickness of the ship transport warehouse for the corresponding first cargo medium and second cargo medium includes:

[0065] If the first and second conditions are met at a certain transfer temperature, that is, the comparison stainless steel can replace the standard stainless steel to accommodate the cargo medium, then whether the corrosion allowance is allowed to be reduced is calculated based on the second corrosion rate.

[0066] In addition, the present invention provides a corrosion assessment system for cargo medium suitability based on a liquid cargo tank of a chemical tanker, the system comprising:

[0067] A first corrosion test calculation module, used to obtain a corrosion test result of a stainless steel standard sample in a first product medium using a first corrosion test method, and then obtain a corresponding first corrosion degree and a first corrosion rate;

[0068] The judgment module is used to determine whether to perform the second corrosion test method according to the corresponding first corrosion degree obtained by the first corrosion test method, specifically:

[0069] A first corrosion degree calculation unit, used for calculating a first corrosion degree of the corresponding stainless steel standard sample according to the corrosion test result of the stainless steel standard sample;

[0070] The judgment unit is used to process the tank thickness of the chemical tanker liquid cargo tank according to the comparison between the first corrosion degree and the second corrosion degree, specifically:

[0071] If the first corrosion degree of the corresponding stainless steel standard sample is large, the stainless steel standard sample and the comparison sample are tested in the second cargo medium using the second corrosion test method under the same parameters to obtain the corrosion test results of the stainless steel standard sample and the comparison sample in the second cargo medium, and then the second corrosion degree and the second corrosion rate corresponding to the second cargo medium are obtained, and the second corrosion degree and the second corrosion rate are used to determine whether to process the tank hull thickness of the chemical tanker liquid cargo tank for the corresponding first cargo medium and the second cargo medium. Otherwise,

[0072] If the first corrosion degree of the corresponding stainless steel standard sample is small, the first corrosion degree and the first corrosion rate are directly used to determine whether to process the thickness of the ship transport warehouse for the corresponding first cargo medium and second cargo medium;

[0073] Among them, the first corrosion test method is a high temperature accelerated corrosion method, and the second corrosion test method is a comparative analysis corrosion method of the transport ship at the actual design loading temperature.

[0074] Beneficial effect: The present invention adopts two different corrosion methods to judge the suitability of stainless steel materials for a certain cargo medium, taking into account the corrosion degree and corrosion rate under two different states, that is, respectively setting the corrosion rate of stainless steel in different liquid cargo tanks at different temperatures and different time nodes for different cargo media; analyzing the corrosion rate to obtain its corresponding index, and performing a suitability assessment based on the index to obtain a suitability assessment result, and determining whether the cargo is suitable for loading the stainless steel in the liquid cargo tank of a chemical tanker according to the suitability assessment result, which makes the present invention accurate and effective in evaluating the suitability corrosion of stainless steel cargo, and is of great significance for the selection of liquid cargo tank materials for chemical tankers and the determination of a list of suitable cargoes.

[0075] The present invention adopts different corrosion degree calculation methods for different corrosion tests. The first corrosion test method is a high temperature test, and the second corrosion test method is a comparative test simulating the actual loading temperature. Obviously, the corrosion degree of stainless steel in the two tests is obviously different. Therefore, different corrosion degree calculation methods enable the corrosion rate and comparative analysis of the stainless steel material of the liquid cargo tank of the chemical tanker when loading different types of goods, thereby greatly improving the accuracy of the assessment of the suitability of the goods and the acceptable corrosion allowance.

[0076] The present invention is based on the proportional relationship between the first corrosion rate and the first corrosion degree under the same conditions, and the present invention selects three identical samples for the same test conditions, based on which the obtained test results are screened, that is, abnormal images after the test in the three identical samples are eliminated, and the normal images are enhanced. In addition, the present invention improves the image enhancement effect by combining the corresponding multiple enhanced images after the image is downsampled, and then realizes the accurate evaluation of the first corrosion degree of the relevant samples through the final enhanced image after the combination.

[0077] When calculating the second corrosion degree, the present invention simultaneously considers the thickness and corrosion area ratio of the standard sample and the comparison sample, and considers the relationship between the ratio and the corresponding threshold value. After analysis, the corresponding weight parameter is obtained, and then the corresponding corrosion degree is obtained in combination with the weight parameter. Therefore, the second corrosion degree obtained by this consideration method is more accurate. Combined with the second corrosion rate, it has important reference value for evaluating whether the stainless steel material can replace the target stainless steel material to be suitable for the cargo medium and evaluating whether the stainless steel material can be used for corrosion allowance calculation when loading the cargo medium. BRIEF DESCRIPTION OF THE DRAWINGS

[0078] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying any creative work.

[0079] Figure 1 This is an example diagram of the macroscopic surface of the original sample of the S32101 test according to the embodiment of the present invention;

[0080] Figure 2 This is an example of the macroscopic surface of the original sample of the S2205 test described in the embodiment of the present invention;

[0081] Figure 3 This is an example diagram of the test process of the second corrosion test according to an embodiment of the present invention;

[0082] Figure 4 This is an example diagram of the macroscopic surface corrosion of S32101 described in an embodiment of the present invention in 98% concentrated sulfuric acid at 30, 40, and 50° C. for 96 hours;

[0083] Figure 5 This is an example diagram of the macroscopic surface corrosion of S2205 described in an embodiment of the present invention in 98% concentrated sulfuric acid at 30, 40, and 50° C. for 96 hours;

[0084] Figure 6 This is a schematic diagram of comparative analysis of the corrosion rates of S32101 and S2205 at 30, 40, and 50° C. 98% concentrated sulfuric acid according to an embodiment of the present invention;

[0085] Figure 7 This is an example diagram of the macroscopic surface of S32101 according to an embodiment of the present invention corroded by 65%-68% nitric acid at 30, 40, and 50° C. for 96 hours;

[0086] Figure 8 An example of the macroscopic surface corrosion of S2205 described in the embodiment of the present invention in 65%-68% nitric acid at 30, 40, and 50° C. for 96 hours;

[0087] Fig. 9 Comparative analysis of the corrosion rates of S32101 and S2205 in 65%-68% nitric acid at 30, 40, and 50°C in the embodiments of the present invention;

[0088] Fig.10 An example of the macroscopic surface corrosion of S32101 described in the embodiment of the present invention in 53% phosphoric acid at 30, 40, and 50° C. for 96 hours;

[0089] Fig.11An example of the macroscopic surface corrosion of S2205 described in the embodiment of the present invention in 53% phosphoric acid at 30, 40, and 50° C. for 96 hours;

[0090] Fig.12 Comparative analysis of the corrosion rates of S32101 and S2205 in 53% phosphoric acid at 30, 40, and 50°C in the embodiments of the present invention;

[0091] Fig.13 This is an example diagram of a standard sample used in the first corrosion test method described in an embodiment of the present invention;

[0092] Fig.14 This is an example diagram of test results of the first corrosion test method according to an embodiment of the present invention;

[0093] Fig.15 This is an example diagram of a test report of the first corrosion test method described in an embodiment of the present invention;

[0094] Fig.16 This is a flow chart of a method for evaluating the suitability of cargo medium corrosion based on a liquid cargo tank of a chemical tanker according to an embodiment of the present invention;

[0095] Fig.17 This is a flow chart of a method for determining a second corrosion test according to a corresponding first corrosion degree obtained by a first corrosion test method according to an embodiment of the present invention. DETAILED DESCRIPTION

[0096] In order to better understand the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0097] like Fig.16 As shown, the present invention provides a method for evaluating the suitability of cargo medium corrosion based on a liquid cargo tank of a chemical tanker, the method comprising the following steps:

[0098] S1 uses a first corrosion test method to obtain a corrosion test result of a stainless steel standard sample in a first product medium, and then obtains a corresponding first corrosion degree and a first corrosion rate;

[0099] S2 determines whether to perform a second corrosion test method according to the first corrosion degree obtained by the first corrosion test method. Specifically, Fig.17 As shown:

[0100] S21 calculates a first corrosion degree of the corresponding stainless steel standard sample according to the corrosion test result of the stainless steel standard sample;

[0101] S22 If the first corrosion degree of the corresponding stainless steel standard sample is large, the stainless steel standard sample and the comparison sample are tested in the second cargo medium using the second corrosion test method under the same parameters to obtain the corrosion test results of the stainless steel standard sample and the comparison sample in the second cargo medium, and then obtain the second corrosion degree and the second corrosion rate corresponding to the second cargo medium, and use the second corrosion degree and the second corrosion rate to determine whether to process the tank hull thickness of the chemical tanker liquid cargo tank for the corresponding first cargo medium and the second cargo medium. Otherwise,

[0102] S23: If the first corrosion degree of the corresponding stainless steel standard sample is small, directly using the first corrosion degree and the first corrosion rate to determine whether to process the thickness of the ship transport warehouse for the corresponding first cargo medium and second cargo medium;

[0103] Among them, the first corrosion test method is a high temperature accelerated corrosion method, and the second corrosion test method is a comparative analysis corrosion method of the transport ship at the actual design loading temperature.

[0104] Furthermore, in this embodiment: the first corrosion test method includes standard sample setting, sample condition setting, corrosion test process and display test results, specifically including:

[0105] Standard sample setting: Cut three duplex stainless steels of the same size and roughness as the stainless steel standard samples, and obtain the exposed surface area S and the mass W before the test. 11 ;

[0106] In this embodiment, the size is set to 20 mm×30 mm, and the surface roughness is the normal delivery state of the steel plant.

[0107] Sample condition setting: including a temperature control device, the temperature control device at least including a heater and a timer; an experimental container containing a first commodity medium, the solution volume of the first commodity medium is obtained according to the surface area of ​​the stainless steel standard sample, and a corresponding stainless steel standard sample is placed in each experimental container.

[0108] The experimental environmental conditions were (23±2)℃, (50±5)%RH.

[0109] This embodiment does not impose any specific restrictions on the temperature control device, as long as it meets the requirements of this test. In other words, a control device and a display screen may be added based on the heater and timer provided in this embodiment.

[0110] Corrosion test process: placing the first cargo medium in the corresponding experimental container; starting the temperature control device to heat the first cargo medium to boiling, after the first cargo medium boils, placing the corresponding stainless steel standard sample, and starting the timing, the continuous boiling time T1 is set to 24h; the time T1 in the embodiment of the present invention can be adjusted according to the ship type and the operating cycle of the ship. For example, domestic trade ships are generally set to 96h, and foreign trade ships will extend the time by 1 times, but the cost of the experiment will be very high due to the long time. The temperature can be increased to a certain extent in exchange for a certain time cost. Specifically, +5℃ can reduce 20% of the time, but the specific situation needs to be determined by customer needs.

[0111] The stainless steel standard sample is taken out from the first product medium, and is brushed in running water to remove corrosion products on the surface of the sample. After drying, the post-test mass W of the stainless steel standard sample is obtained. 12 ;

[0112] Display test results: Calculate the first corrosion degree according to the image of the stainless steel standard sample after the test and obtain the first corrosion rate according to the corresponding mass.

[0113] Further, in this embodiment, the first product medium includes: formic acid with a mass percentage concentration of not less than 98% m / m; capric acid with a mass percentage concentration of not less than 99% m / m; saturated citric acid aqueous solution lactic acid with a mass percentage concentration between 85% and 90% m / m; saturated urea aqueous solution acetic anhydride with a mass percentage concentration of not less than 98.5% m / m; acrylic acid with a mass percentage concentration greater than 99% m / m; saturated aluminum sulfate solution with a mass content of 200 g / L; saturated aluminum chloride / hydrochloric acid solution; saturated ammonium sulfate aqueous solution; ammonium thiosulfate solution with a mass percentage concentration of 60% m / m; saturated ferric chloride / hydrochloric acid solution; saturated Aqueous sodium hydrogen sulphate solution; n-butyric acid at 99.5% m / m by mass; chloroacetic acid at 98% m / m by mass; 3-chloropropionic acid at 98% m / m by mass; a mixture of n-pentanoic acid at 64% m / m and 2-methylbutyric acid at 36% m / m by mass; phosphoric acid at greater than 99% m / m by mass; propionic acid at greater than 99.5% m / m by mass; trimethylacetic acid at 99% m / m by mass; saturated aqueous sodium hydroxide solution; allyl chloride at 98% m / m by mass and benzyl chloride at greater than 99.0% m / m by mass.

[0114] In this embodiment, the experimental process and results corresponding to the first corrosion test method are specifically as follows:

[0115] The reagents used include:

[0116] Reagent 2: Formic acid (≥98% m / m)

[0117] Reagent 4: Decanoic acid (99% m / m)

[0118] Reagent 5: Saturated citric acid aqueous solution Reagent 6: Lactic acid (85% to 90% m / m)

[0119] Reagent 7: Saturated urea aqueous solution

[0120] Reagent 8: Acetic anhydride (≥98.5% m / m)

[0121] Reagent 9: Acrylic acid (>99% m / m)

[0122] Reagent 10: Saturated aluminum sulfate solution (200 g / L)

[0123] Reagent 11: Saturated aluminum chloride / hydrochloric acid solution

[0124] Reagent 12: Saturated ammonium sulfate aqueous solution

[0125] Reagent 13: Ammonium thiosulfate solution (60% m / m)

[0126] Reagent 16: Saturated ferric chloride / hydrochloric acid solution

[0127] Reagent 17: Saturated sodium bisulfite aqueous solution

[0128] Reagent 18: n-Butyric acid (99.5% m / m)

[0129] Reagent 19: Chloroacetic acid (98% m / m)

[0130] Reagent 20: 3-Chloropropionic acid (98% m / m)

[0131] Reagent 22: mixture of n-valeric acid (64% m / m) and 2-methylbutyric acid (36% m / m)

[0132] Reagent 23: Phosphoric acid (≥99% m / m)

[0133] Reagent 24: Propionic acid (≥99.5% m / m)

[0134] Reagent 25: Trimethylacetic acid (99% m / m)

[0135] Reagent 26: Saturated sodium hydroxide aqueous solution

[0136] Reagent 28: Allyl gas (98% m / m)

[0137] Reagent 29: Benzyl chloride (>99.0% m / m)

[0138] The corresponding test results and test reports are as follows: Fig.13 , Fig.14 and 15 shown.

[0139] Among them, method 1 is the first corrosion test method mentioned above, and method 2 is: immersion at 50℃

[0140] Immerse the test sample completely in the test reagent and keep the temperature at 50℃

[0141] Method 3: Soak at room temperature

[0142] The test sample is completely immersed in the test reagent and the temperature is maintained at room temperature. The laboratory environmental conditions of the above method are: (23±2)°C, (50±5)%RH.

[0143] Furthermore, this embodiment also includes:

[0144] The calculation formula of the first corrosion rate is expressed as:

[0145]

[0146] The first corrosion rate is used as the first condition for evaluating whether the stainless steel material corresponding to the stainless steel standard sample is suitable for the corresponding product medium, and it is set that when CR1≤100g / (m 2 h), the stainless steel material corresponding to the stainless steel standard sample meets the first condition.

[0147] Further, including:

[0148] The corresponding first corrosion degree obtained according to the first corrosion test method includes:

[0149] Preprocessing the images of the stainless steel standard samples obtained according to the first corrosion test method at different times, wherein the preprocessing includes image screening, image downsampling, and image enhancement performed according to different commodity media, and the different times refer to the time corresponding to the completion of the first corrosion test method, and the image enhancement is obtained according to the result of image downsampling;

[0150] Calculate the information entropy corresponding to the enhanced image after image enhancement under different first commodity media, obtain the weight corresponding to the enhanced image according to the information entropy, and fuse the enhanced image corresponding to each image according to the weight to obtain the final enhanced image;

[0151] Obtaining the eroded area corresponding to the final enhanced image, and obtaining the pixel value of each pixel in the eroded area;

[0152] Calculate the corrosion intensity of the corresponding stainless steel standard sample under the commodity medium according to the pixel value of each pixel point and the corresponding color value;

[0153] Set the corrosion level, and determine the first corrosion degree according to the corrosion intensity and the preset corrosion intensity threshold. If the corrosion intensity threshold is set to [0,10], the corresponding corrosion level is less than 5, and is set as the first corrosion degree is small. The corresponding corrosion level is greater than or equal to 5, and is set as the first corrosion degree is large.

[0154] Further, including:

[0155] Among them, image screening specifically includes: eliminating the abnormal first corrosion rates obtained by the first corrosion test method for three stainless steel standard samples under the same first commodity medium, and deleting the sample images corresponding to the abnormal first corrosion rates. The method for determining the abnormal first corrosion rates is: calculating the pairwise differences among the three first corrosion rates obtained by the first corrosion test method for the three stainless steel standard samples, finding the corresponding two first corrosion rates with the smallest absolute value of the difference, and obtaining the corresponding abnormal first corrosion rates according to the box plot method.

[0156] Further, including:

[0157] The directly using the first corrosion degree and the first corrosion rate to judge whether to process the thickness of the ship transport warehouse for the corresponding first cargo medium and second cargo medium includes:

[0158] The corrosion level serves as the second condition for evaluating whether the stainless steel material corresponding to the stainless steel standard sample is suitable for the corresponding cargo medium. When the corrosion level is not greater than 3, it meets the second condition. Only when both the first and second conditions are met can it be determined that the chemical tanker liquid cargo tank corresponding to the stainless steel standard sample is suitable for the corresponding cargo medium, and whether the corrosion allowance is allowed to be reduced is obtained based on the first corrosion rate.

[0159] In this embodiment, the second corrosion test method also includes: standard sample setting, sample condition setting, corrosion test process and display test results, specifically:

[0160] Standard sample setting: three duplex stainless steels of two different types with the same size and roughness are cut, and the stainless steel in the first corrosion test method is used as the stainless steel standard sample, and another different type of duplex stainless steel is used as a comparison sample, thereby obtaining the exposed surface area S and the mass W before the test 21 ;

[0161] In this embodiment, the comparison sample is S32101 and the standard sample is S2205, because S2205 is recognized as the most corrosion-resistant liquid cargo tanker chemical tanker on the market, and major chemical ship owners are willing to use it as the liquid cargo tank material of foreign trade chemical tankers, and at the same time, it has been allowed to reduce the thickness of the plate to reduce the corrosion allowance. This material has been in service for more than 15 years, and there is no record of cargo operation corrosion in the records of CCS, but the price is very expensive. Therefore, nickel-saving duplex stainless steel was developed, and the price is about 13,000 yuan cheaper per ton. Therefore, the evaluation method is to evaluate 32101 (or cheaper and more advanced stainless steel materials in the future) to replace S2205, and reduce the thickness of the plate to help shipowners save money.

[0162] And specifically:

[0163] 27 20mm×30mm pitting corrosion specimens were cut from the head of the S32101 and S2205 steel plates. The surface roughness was in the normal delivery state of the steel plant, and pickling and passivation were not performed for this corrosion. Corrosion simulation experiments were carried out at 30, 40, and 50°C in three corrosion reagents: 98% concentrated sulfuric acid, 65%-68% nitric acid, and 53% phosphoric acid (all of laboratory-grade purity), and the corrosion rate and surface macroscopic photograph results were provided. Among them, the corrosion rate and surface macroscopic photograph results of S2205 stainless steel were provided as a comparative analysis of S32101. The corrosion time was 96h. The original macroscopic surface photograph is shown in Figure 1-2 , the test process is shown in Figure 3 .

[0164] Sample condition setting: including a temperature control device, the temperature control device at least including a heater and a timer; an experimental container containing a second commodity medium, the solution volume of the second commodity medium is obtained according to the surface area of ​​the stainless steel standard sample and the comparative sample, and a corresponding stainless steel standard sample and comparative sample are placed in each experimental container;

[0165] Corrosion test process: Place the second product medium in the corresponding experimental container; start the temperature control device to heat the second product medium to the corresponding loading temperature, put in the corresponding stainless steel standard sample and comparison sample, start timing, and let it stand for T 21 After 1 hour, the stainless steel standard sample and the comparative sample were taken out, cleaned and weighed to obtain W 22 ;

[0166] Then, the corresponding stainless steel standard samples and comparison samples were placed back in the above test environment and left to stand for T 22 After 12 hours, the stainless steel standard sample was taken out, cleaned and weighed to obtain W. 23 ;

[0167] Display test results: calculate the second corrosion degree based on the tested stainless steel standard sample and the comparison sample, and obtain the second corrosion rate at different transfer temperatures and under different second cargo media based on the corresponding mass.

[0168] Furthermore, this embodiment also includes:

[0169] The second cargo medium includes: concentrated sulfuric acid with a mass concentration of 98% m / m, nitric acid with a mass concentration between 65%-68% m / m, and phosphoric acid with a mass concentration of 53% m / m, and the loading temperatures include: 30°C, 40°C and 50°C.

[0170] The specific experimental results and evaluation and analysis process are as follows:

[0171] (1) Concentrated sulfuric acid (98%)

[0172] The results of the 98% concentrated sulfuric acid corrosion test of S32101 and S2205 are as follows: Figure 4 , 5 The corrosion rate comparison is shown in Table 1 and Figure 6 shown.

[0173] After 96 hours at 30℃ and 98% concentrated sulfuric acid, the overall corrosion conditions of S32101 and S2205 are good and basically the same. The average corrosion rates of S32101 and S2205 at 30℃ and 98% concentrated sulfuric acid for 96 hours are 27.0 and 13.4mdd, respectively, and the average corrosion rate of S32101 is higher than that of S2205. The annual corrosion thinning rates of S32101 and S2205 are 0.126 and 0.019mm / a.

[0174] After 96 hours at 40℃ and 98% concentrated sulfuric acid, the surface corrosion of S32101 was good, and corrosion marks appeared locally on S2205. The average corrosion rates of S32101 and S2205 at 40℃ and 98% concentrated sulfuric acid for 96 hours were 24.9 and 25.2 mdd, respectively, and the average corrosion rate of S32101 was basically consistent with that of S2205. The annual corrosion thinning rates of S32101 and S2205 were 0.116 and 0.118 mm / a.

[0175] After 96 hours at 50℃ and 98% concentrated sulfuric acid, the overall corrosion conditions of S32101 and S2205 are good and basically the same. The average corrosion rates of S32101 and S2205 at 50℃ and 98% concentrated sulfuric acid for 96 hours are 59.9 and 85.7mdd respectively, and the average corrosion rate of S32101 is slightly lower than that of S2205. The annual corrosion thinning rates of S32101 and S2205 are 0.280 and 0.401mm / a.

[0176] Table 1: Corrosion rate of S32101 and S2205 in 98% concentrated sulfuric acid at 30, 40, 50℃ for 96h

[0177]

[0178] like Figure 6 As shown, the corrosion rates of S32101 and S2205 in 98% concentrated sulfuric acid at 30, 40 and 50°C are compared and analyzed. It can be seen that the corrosion rate of the standard sample in 98% concentrated sulfuric acid at 30°C is higher, and the corrosion rate of the comparison sample in 98% concentrated sulfuric acid at 40 and 50°C is higher.

[0179] (2) Nitric acid (65%-68%)

[0180] The results of the 65%-68% nitric acid comparative corrosion test of S32101 and S2205 are as follows: Figure 7 , 8 The corrosion rate comparison is shown in Table 2 and Fig. 9 shown.

[0181] After 96 hours at 30℃ 65%-68% nitric acid, the overall surface corrosion of S32101 and S2205 is good and basically the same. The average corrosion rates of S32101 and S2205 at 30℃ 65%-68% nitric acid for 96 hours are 1.2 and 0.9mdd respectively, and the average corrosion rate of S32101 is slightly higher than that of S2205. The annual corrosion thinning rates of S32101 and S2205 are 0.006 and 0.004mm / a.

[0182] After 96 hours at 40℃ 65%-68% nitric acid, corrosion marks appeared locally on S32101 and S2205. The average corrosion rates of S32101 and S2205 at 40℃ 65%-68% nitric acid for 96 hours were 1.5 and 1.4 mdd, respectively, and the average corrosion rate of S32101 was slightly higher than that of S2205. The annual corrosion thinning rates of S32101 and S2205 were 0.007 and 0.007 mm / a.

[0183] After 96 hours at 50℃ and 65%-68% nitric acid, S32101 showed large-area corrosion, and S2205 showed local corrosion marks. The average corrosion rates of S32101 and S2205 at 50℃ and 65%-68% nitric acid for 96 hours were 4.3 and 3.2 mdd, respectively, and the average corrosion rate of S32101 was slightly higher than that of S2205. The annual corrosion thinning rates of S32101 and S2205 were 0.020 and 0.015 mm / a.

[0184] Table 2: Corrosion rate of S32101 and S2205 in 65%-68% nitric acid at 30, 40, 50°C for 96h

[0185]

[0186] (3) Phosphoric acid (53%)

[0187] The results of the 53% phosphoric acid comparative corrosion test of S32101 and S2205 are as follows: Fig.10 , 11 The corrosion rate comparison is shown in Table 3 and Fig.12 shown.

[0188] After 96 hours at 30℃53% phosphoric acid, the overall corrosion conditions of S32101 and S2205 are good and basically the same. The average corrosion rates of S32101 and S2205 at 30℃53% phosphoric acid for 96 hours are 0.7 and 0.8mdd respectively, and the average corrosion rate of S32101 is slightly lower than that of S2205. The annual corrosion thinning rates of S32101 and S2205 are 0.003 and 0.004mm / a.

[0189] After 96 hours at 40℃53% phosphoric acid, the overall corrosion conditions of S32101 and S2205 are good and basically the same. The average corrosion rates of S32101 and S2205 at 40℃53% phosphoric acid for 96 hours are 0.7 and 1.2mdd respectively, and the average corrosion rate of S32101 is lower than that of S2205. The annual corrosion thinning rates of S32101 and S2205 are 0.003 and 0.006mm / a.

[0190] After 96 hours at 50℃53% phosphoric acid, the overall corrosion conditions of S32101 and S2205 are good and basically the same. The average corrosion rates of S32101 and S2205 at 50℃53% phosphoric acid for 96 hours are 2.3 and 1.1mdd respectively, and the average corrosion rate of S32101 is higher than that of S2205. The annual corrosion thinning rates of S32101 and S2205 are 0.010 and 0.004mm / a.

[0191] Table 3: Corrosion rate of S32101 and S2205 in 53% phosphoric acid at 30, 40, 50°C for 96h

[0192]

[0193]

[0194] Based on the above analysis and comparison of the simulated corrosion results of S32101 and S2205, the following conclusions can be drawn as a basis for drawing review:

[0195] (1) 98% concentrated sulfuric acid, 65%-68% nitric acid and 53% phosphoric acid can be added to the list of suitable goods for S32101 produced by the steel plant.

[0196] (2) When S32101 and S2205 are loaded with 98% concentrated sulfuric acid, the cargo tank temperature must be below 40°C during operation.

[0197] (3) When S32101 is loaded with 65%-68% nitric acid, the temperature of the cargo tank must be below 40°C during operation; when S2205 is loaded with 65%-68% nitric acid, the temperature of the cargo tank must be below 50°C during operation.

[0198] (4) When S32101 and S2205 are loaded with 53% phosphoric acid, the cargo tank temperature must be below 50°C during operation.

[0199] (5) When S32101 is loaded with the above-mentioned 98% concentrated sulfuric acid, 65%-68% nitric acid and 53% phosphoric acid and the operating quality is strictly controlled, the structural calculation can be carried out according to zero corrosion allowance.

[0200] In order to ensure the actual loading and operation of three strong acids, namely 98% concentrated sulfuric acid, 65%-68% nitric acid and 53% phosphoric acid, in this embodiment, CCS will monitor the corrosion of the liquid cargo tanks after the first loading and unloading of the chemical tankers built with this material.

[0201] In this experiment, all samples were not pickled and passivated, so if the samples were pickled and passivated, the corrosion rate would be smaller (more ideal) than the current result.

[0202] There were large deviations in two sets of data in this experimental result. The subsequent two sets of data will be re-verified to see if there are any human errors, but the above-mentioned basis for drawing review remains valid.

[0203] Furthermore, the above includes:

[0204] The calculation formula of the second corrosion rate corresponding to different standing times is expressed as:

[0205]

[0206] According to the above calculation formula, the corrosion rates of different second cargo media of the stainless steel standard sample at different loading temperatures are obtained; and the corrosion rates of different second cargo media of the comparison sample at different loading temperatures are obtained, and the corrosion rates corresponding to the two samples are compared and analyzed, and then combined with the loading temperature as the first condition for evaluating whether the comparison stainless steel can replace the standard stainless steel to be suitable for the cargo medium.

[0207] Furthermore, this embodiment also includes:

[0208] The calculation of the second corrosion degree according to the tested stainless steel standard sample and the comparative sample comprises:

[0209] Obtain the thickness of the standard sample and the comparison sample obtained from the same product medium at the same loading temperature after the test. The thickness of the single standard sample is recorded as D1, and the thickness of the comparison sample is recorded as D2;

[0210] The standard thickness under the same conditions obtained according to relevant standards is recorded as standard H;

[0211] Calculate the difference between the thickness D1 and D2 and the standard thickness H for comparison; specifically, if |D1-H|≤|D2-H|, then the first weight of the standard sample is greater than the corresponding weight of the comparison sample, and the first weight of the standard sample is a parameter for measuring the adaptability of the standard sample and the comparison sample;

[0212] According to the corrosion areas corresponding to the standard sample and the comparison sample obtained for the same product medium at the same loading temperature, the corrosion area occupancy rates are obtained, which are recorded as R1 and R2 respectively. If R1≤R2 and both are less than the occupancy setting threshold, this threshold is set to about 20%, and the specific values ​​are not displayed in this embodiment, then the second weight of the standard sample is greater than the corresponding weight of the comparison sample, and the second weight of the standard sample is a parameter for measuring the adaptability of the standard sample and the comparison sample; if R1≤R2 and R2 is not less than the occupancy setting threshold, then the second weight of the comparison sample is set to zero, if R1≤R2 and both are not less than the occupancy setting threshold, then neither the standard sample nor the comparison sample is used as a suitable material, if R1>R2 and both are less than the occupancy setting threshold, then the second weight of the comparison sample is greater than the corresponding weight of the standard sample, if R1>R2 and R1 is not less than the occupancy setting threshold, then the second weight of the standard sample is set to zero, if R1>R2 and both are not less than the occupancy setting threshold, then neither the standard sample nor the comparison sample can be used as a suitable material;

[0213] The second corrosion degree of the standard sample and the comparison sample to a certain cargo medium at different loading temperatures is obtained comprehensively according to the first adaptation weight and the second adaptation weight, which serves as the second condition for whether the comparison stainless steel can replace the standard stainless steel to be suitable for the cargo medium.

[0214] Furthermore, this embodiment also includes:

[0215] Using the second corrosion degree and the second corrosion rate to determine whether to process the thickness of the ship transport warehouse for the corresponding first cargo medium and second cargo medium includes:

[0216] If the first and second conditions are met at a certain transfer temperature, that is, the comparison stainless steel can replace the standard stainless steel to accommodate the cargo medium, then whether the corrosion allowance is allowed to be reduced is calculated based on the second corrosion rate.

[0217] In this embodiment, after calculating the mdd, there is a conversion formula to convert it into mm / year, which is the number of millimeters thinned each year. The replacement life of the ship's plate is about 13-20 years. Therefore, by matching the quarterly loading and operating time planned by the shipowner with the thinning at the relevant temperature, it can be determined whether the material 1. can load the medium, 2. what temperature must be lower than when loading the medium, and 3. whether the corrosion allowance is allowed.

[0218] The present invention evaluates whether the stainless steel material is suitable for loading the goods according to the surface corrosion conditions and corrosion rates of the standard samples obtained by the first corrosion test method. According to the surface corrosion conditions and corrosion rates of the standard samples and the comparison samples obtained by the first corrosion test method, it is evaluated whether the stainless steel material can replace the target stainless steel material to load the goods medium. And according to the surface corrosion conditions and corrosion rates of the standard samples and the comparison samples obtained by the first corrosion test method, it is evaluated whether the stainless steel material can perform zero corrosion allowance calculation when loaded with the goods medium.

[0219] In addition, the present invention provides a corrosion assessment system for cargo medium suitability based on a liquid cargo tank of a chemical tanker, the system comprising:

[0220] A first corrosion test calculation module, used to obtain a corrosion test result of a stainless steel standard sample in a first product medium using a first corrosion test method, and then obtain a corresponding first corrosion degree and a first corrosion rate;

[0221] The judgment module is used to determine whether to perform the second corrosion test method according to the corresponding first corrosion degree obtained by the first corrosion test method, specifically:

[0222] A first corrosion degree calculation unit, used for calculating a first corrosion degree of the corresponding stainless steel standard sample according to the corrosion test result of the stainless steel standard sample;

[0223] The judgment unit is used to process the tank thickness of the chemical tanker liquid cargo tank according to the comparison between the first corrosion degree and the second corrosion degree, specifically:

[0224] If the first corrosion degree of the corresponding stainless steel standard sample is large, the stainless steel standard sample and the comparison sample are tested in the second cargo medium using the second corrosion test method under the same parameters to obtain the corrosion test results of the stainless steel standard sample and the comparison sample in the second cargo medium, and then the second corrosion degree and the second corrosion rate corresponding to the second cargo medium are obtained, and the second corrosion degree and the second corrosion rate are used to determine whether to process the tank hull thickness of the chemical tanker liquid cargo tank for the corresponding first cargo medium and the second cargo medium. Otherwise,

[0225] If the first corrosion degree of the corresponding stainless steel standard sample is small, the first corrosion degree and the first corrosion rate are directly used to determine whether to process the thickness of the ship transport warehouse for the corresponding first cargo medium and second cargo medium;

[0226] Among them, the first corrosion test method is a high temperature accelerated corrosion method, and the second corrosion test method is a comparative analysis corrosion method of the transport ship at the actual design loading temperature.

[0227] Other technical features of the cargo medium suitability corrosion assessment system based on the liquid cargo tank of a chemical tanker described in the present invention are similar to the corresponding method and will not be repeated here.

[0228] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0229] Obviously, those skilled in the art can make various changes and modifications to the embodiments of the present invention without departing from the spirit and scope of the embodiments of the present invention. Thus, if these modifications and variations of the embodiments of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A corrosion assessment method for suitability of stainless steel materials in liquid cargo tanks of chemical tankers, characterized in that: The method includes: Using a first corrosion test method to obtain corrosion test results of a standard stainless steel sample in a first product medium, and then obtaining a corresponding first corrosion degree and a first corrosion rate; Determine whether to perform the second corrosion test method according to the first corrosion degree corresponding to the first corrosion test method, specifically: Calculate the first corrosion degree of the corresponding stainless steel standard sample according to the corrosion test result of the stainless steel standard sample; If the first corrosion degree of the corresponding stainless steel standard sample is large, the stainless steel standard sample and the comparison sample are tested in the second cargo medium using the second corrosion test method under the same parameters to obtain the corrosion test results of the stainless steel standard sample and the comparison sample in the second cargo medium, and then the second corrosion degree and the second corrosion rate corresponding to the second cargo medium are obtained, and the second corrosion degree and the second corrosion rate are used to determine whether to process the tank hull thickness of the chemical tanker liquid cargo tank for the corresponding first cargo medium and the second cargo medium. Otherwise, If the first corrosion degree of the corresponding stainless steel standard sample is small, the first corrosion degree and the first corrosion rate are directly used to determine whether to process the thickness of the ship transport warehouse for the corresponding first cargo medium and second cargo medium; Among them, the first corrosion test method is a high temperature accelerated corrosion method, and the second corrosion test method is a comparative analysis corrosion method of the transport ship at the actual design loading temperature.

2. The method for evaluating the suitability of cargo medium for a chemical tanker liquid cargo tank according to claim 1 is characterized in that: The first corrosion test method includes standard sample setting, sample condition setting, corrosion test process and display test results, specifically: Standard sample setting: Cut three duplex stainless steels of the same size and roughness as the stainless steel standard samples, and obtain the exposed surface area S and the mass W before the test. 11 ; Sample condition setting: including a temperature control device, the temperature control device at least including a heater and a timer; an experimental container containing a first commodity medium, the solution volume of the first commodity medium is obtained according to the surface area of ​​the stainless steel standard sample, and a corresponding stainless steel standard sample is placed in each experimental container; Corrosion test process: placing the first product medium in a corresponding test container; Start the temperature control device to heat the first commodity medium to boiling. After the first commodity medium boils, put the corresponding stainless steel standard sample in and start timing. The continuous boiling time T1 is set to 24 hours. The stainless steel standard sample is taken out from the first product medium, and is brushed in running water to remove corrosion products on the surface of the sample. After drying, the post-test mass W of the stainless steel standard sample is obtained. 12 ; Display test results: Calculate the first corrosion degree according to the image of the stainless steel standard sample after the test and obtain the first corrosion rate according to the corresponding mass.

3. The method for evaluating the suitability of cargo medium for a chemical tanker liquid cargo tank according to claim 2 is characterized in that: The first product medium includes: formic acid with a mass percentage concentration of not less than 98% m / m; capric acid with a mass percentage concentration of not less than 99% m / m; saturated citric acid aqueous solution lactic acid with a mass percentage concentration between 85% and 90% m / m; saturated urea aqueous solution acetic anhydride with a mass percentage concentration of not less than 98.5% m / m; acrylic acid with a mass percentage concentration greater than 99% m / m; saturated aluminum sulfate solution with a mass content of 200g / L; saturated aluminum chloride / hydrochloric acid solution; saturated ammonium sulfate aqueous solution; ammonium thiosulfate solution with a mass percentage concentration of 60% m / m; saturated ferric chloride / hydrochloric acid solution; saturated sodium bisulfite aqueous solution; liquid; 99.5% m / m n-butyric acid; 98% m / m chloroacetic acid; 98% m / m 3-chloropropionic acid; a mixture of 64% m / m n-pentanoic acid and 36% m / m 2-methylbutyric acid; phosphoric acid greater than 99% m / m; propionic acid greater than 99.5% m / m; trimethylacetic acid at 99% m / m; saturated aqueous sodium hydroxide solution; 98% m / m allyl chloride and greater than 99.0% m / m benzyl chloride.

4. The method for evaluating the suitability of cargo medium for chemical tanker liquid cargo tanks according to claim 3 is characterized in that: The calculation formula of the first corrosion rate is expressed as: The first corrosion rate is used as the first condition for evaluating whether the stainless steel material corresponding to the stainless steel standard sample is suitable for the corresponding product medium, and it is set that when CR1≤100g / (m 2 h), the stainless steel material corresponding to the stainless steel standard sample meets the first condition.

5. The method for evaluating the suitability of cargo medium for a chemical tanker liquid cargo tank according to claim 4 is characterized in that: The corresponding first corrosion degree obtained according to the first corrosion test method includes: Preprocessing the images of the stainless steel standard samples obtained according to the first corrosion test method at different times, wherein the preprocessing includes image screening, image downsampling, and image enhancement performed according to different commodity media, and the different times refer to the time corresponding to the completion of the first corrosion test method, and the image enhancement is obtained according to the result of image downsampling; Calculate the information entropy corresponding to the enhanced image after image enhancement under different first commodity media, obtain the weight corresponding to the enhanced image according to the information entropy, and fuse the enhanced image corresponding to each image according to the weight to obtain the final enhanced image; Obtaining the eroded area corresponding to the final enhanced image, and obtaining the pixel value of each pixel in the eroded area; Calculate the corrosion intensity of the corresponding stainless steel standard sample under the commodity medium according to the pixel value of each pixel point and the corresponding color value; Set the corrosion level, and determine the first corrosion degree according to the corrosion intensity and the preset corrosion intensity threshold. If the corrosion intensity threshold is set to [0,10], the corresponding corrosion level is less than 5, and is set as the first corrosion degree is small. The corresponding corrosion level is greater than or equal to 5, and is set as the first corrosion degree is large.

6. The method for evaluating the suitability of cargo medium for chemical tanker liquid cargo tanks according to claim 5 is characterized in that: The image screening specifically includes: eliminating the abnormal first corrosion rates obtained by the first corrosion test method for three stainless steel standard samples under the same first commodity medium, and deleting the sample images corresponding to the abnormal first corrosion rates. The method for determining the abnormal first corrosion rates is: calculating the pairwise differences among the three first corrosion rates obtained by the first corrosion test method for the three stainless steel standard samples, finding the two first corrosion rates corresponding to the smallest absolute value of the difference, and obtaining the corresponding abnormal first corrosion rates according to the box plot method.

7. The method for evaluating the suitability of cargo medium for chemical tanker liquid cargo tanks according to claim 5 is characterized in that: The directly using the first corrosion degree and the first corrosion rate to judge whether to process the thickness of the ship transport warehouse for the corresponding first cargo medium and second cargo medium includes: The corrosion level serves as the second condition for evaluating whether the stainless steel material corresponding to the stainless steel standard sample is suitable for the corresponding cargo medium. When the corrosion level is not greater than 3, it meets the second condition. Only when both the first and second conditions are met can it be determined that the chemical tanker liquid cargo tank corresponding to the stainless steel standard sample is suitable for the corresponding cargo medium, and whether the corrosion allowance is allowed to be reduced is obtained based on the first corrosion rate.

8. The method for evaluating the suitability of cargo medium for a chemical tanker liquid cargo tank according to claim 1 is characterized in that: The second corrosion test method includes standard sample setting, sample condition setting, corrosion test process and display test results, specifically: Standard sample setting: three duplex stainless steels of two different types with the same size and roughness are cut, and the stainless steel in the first corrosion test method is used as the stainless steel standard sample, and another different type of duplex stainless steel is used as a comparison sample, thereby obtaining the exposed surface area S and the mass W before the test 21 ; Sample condition setting: including a temperature control device, the temperature control device at least including a heater and a timer; an experimental container containing a second commodity medium, the solution volume of the second commodity medium is obtained according to the surface area of ​​the stainless steel standard sample and the comparative sample, and a corresponding stainless steel standard sample and comparative sample are placed in each experimental container; Corrosion test process: placing the second cargo medium in a corresponding test container; Start the temperature control device to heat the second cargo medium to the corresponding loading temperature, put in the corresponding stainless steel standard sample and comparison sample, start timing, and let it stand for T 21 After 1 hour, the stainless steel standard sample and the comparative sample were taken out, cleaned and weighed to obtain W 22 ; Then, the corresponding stainless steel standard samples and comparison samples were placed back in the above test environment and left to stand for T 22 After 12 hours, the stainless steel standard sample was taken out, cleaned and weighed to obtain W. 23 ; Display test results: calculate the second corrosion degree based on the tested stainless steel standard sample and the comparison sample, and obtain the second corrosion rate at different transfer temperatures and under different second cargo media based on the corresponding mass.

9. The method for evaluating the suitability of cargo medium for a chemical tanker liquid cargo tank according to claim 8 is characterized in that: The second cargo medium includes: concentrated sulfuric acid with a mass concentration of 98% m / m, nitric acid with a mass concentration between 65%-68% m / m, and phosphoric acid with a mass concentration of 53% m / m, and the loading temperatures include: 30°C, 40°C and 50°C.

10. The method for evaluating the suitability of cargo medium for a chemical tanker liquid cargo tank according to claim 8 is characterized in that: The calculation formula of the second corrosion rate corresponding to different standing times is expressed as: According to the above calculation formula, the corrosion rates of different second cargo media of the stainless steel standard sample at different loading temperatures are obtained; and the corrosion rates of different second cargo media of the comparison sample at different loading temperatures are obtained, and the corrosion rates corresponding to the two samples are compared and analyzed, and then combined with the loading temperature as the first condition for evaluating whether the comparison stainless steel can replace the standard stainless steel to be suitable for the cargo medium.

11. The method for evaluating the suitability of cargo medium for a chemical tanker liquid cargo tank according to claim 10 is characterized in that: The calculation of the second corrosion degree according to the tested stainless steel standard sample and the comparative sample comprises: Obtain the thickness of the standard sample and the comparison sample obtained from the same product medium at the same loading temperature after the test. The thickness of the single standard sample is recorded as D1, and the thickness of the comparison sample is recorded as D2; The standard thickness under the same conditions obtained according to relevant standards is recorded as standard H; Calculate the difference between the thickness D1 and D2 and the standard thickness H for comparison; specifically, if |D1-H|≤|D2-H|, then the first weight of the standard sample is greater than the corresponding weight of the comparison sample, and the first weight of the standard sample is a parameter for measuring the adaptability of the standard sample and the comparison sample; According to the corrosion area corresponding to the standard sample and the comparison sample obtained from the same cargo medium at the same loading temperature, the corrosion area occupancy rate is obtained, which is recorded as R1 and R2 respectively. If R1≤R2 and both are less than the occupancy setting threshold, the second adaptation weight of the standard sample is greater than the corresponding weight of the comparison sample, and the second adaptation weight is a parameter for measuring the adaptation capabilities of the standard sample and the comparison sample; If R1≤R2 and R2 is not less than the occupancy setting threshold, the second weight of the comparison sample is set to zero. If R1≤R2 and both are not less than the occupancy setting threshold, the standard sample and the comparison sample are not used as suitable materials. If R1>R2 and both are less than the occupancy setting threshold, the second weight of the comparison sample is greater than the corresponding weight of the standard sample. If R1>R2 and R1 is not less than the occupancy setting threshold, the second weight of the standard sample is set to zero. If R1>R2 and both are not less than the occupancy rate setting threshold, then neither the standard sample nor the comparison sample can be used as suitable materials; The second corrosion degree of the standard sample and the comparison sample to a certain cargo medium at different loading temperatures is obtained comprehensively according to the first adaptation weight and the second adaptation weight, which serves as the second condition for whether the comparison stainless steel can replace the standard stainless steel to be suitable for the cargo medium.

12. The method for evaluating the suitability of cargo medium for a chemical tanker liquid cargo tank according to claim 11 is characterized in that: Using the second corrosion degree and the second corrosion rate to determine whether to process the thickness of the ship transport warehouse for the corresponding first cargo medium and second cargo medium includes: If the first and second conditions are met at a certain transfer temperature, that is, the comparison stainless steel can replace the standard stainless steel to accommodate the cargo medium, then whether the corrosion allowance is allowed to be reduced is calculated based on the second corrosion rate.

13. A corrosion assessment system for cargo medium suitability based on a chemical tanker liquid cargo tank, characterized in that: The system includes: A first corrosion test calculation module, used to obtain a corrosion test result of a stainless steel standard sample in a first product medium using a first corrosion test method, and then obtain a corresponding first corrosion degree and a first corrosion rate; The judgment module is used to determine whether to perform the second corrosion test method according to the corresponding first corrosion degree obtained by the first corrosion test method, specifically: A first corrosion degree calculation unit, used for calculating a first corrosion degree of the corresponding stainless steel standard sample according to the corrosion test result of the stainless steel standard sample; The judgment unit is used to process the tank thickness of the chemical tanker liquid cargo tank according to the comparison between the first corrosion degree and the second corrosion degree, specifically: If the first corrosion degree of the corresponding stainless steel standard sample is large, the stainless steel standard sample and the comparison sample are tested in the second cargo medium using the second corrosion test method under the same parameters to obtain the corrosion test results of the stainless steel standard sample and the comparison sample in the second cargo medium, and then the second corrosion degree and the second corrosion rate corresponding to the second cargo medium are obtained, and the second corrosion degree and the second corrosion rate are used to determine whether to process the tank hull thickness of the chemical tanker liquid cargo tank for the corresponding first cargo medium and the second cargo medium. Otherwise, If the first corrosion degree of the corresponding stainless steel standard sample is small, the first corrosion degree and the first corrosion rate are directly used to determine whether to process the thickness of the ship transport warehouse for the corresponding first cargo medium and second cargo medium; Among them, the first corrosion test method is a high temperature accelerated corrosion method, and the second corrosion test method is a comparative analysis corrosion method of the transport ship at the actual design loading temperature.

Citation Information

Patent Citations

  • Method for detecting bone china glaze chemical corrosion resistance through 45-degree mirror glossiness loss measurement method

    CN107894388A

  • Corrosion resistance evaluation method of stainless steel material

    CN111307703A

  • Method and device for predicting corrosion-resistant life of metal material and electronic equipment

    CN113138158A

  • Method for detecting uniform corrosion resistance of stainless steel

    CN114544476A

  • Hull surface corrosion degree evaluation method based on image processing

    CN114841903A